Pengaruh Corporate Governance, Profitabilitas Dan Likuiditas Terhadap Penghindaran Pajak Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2012-2016 - Suri Mahrani (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2019)
This research was motivated by the big news of tax evasion cases in the world including Indonesia, of course the Panama Papers and Paradise Papers. Specifically, many mining companies in Indonesia avoid taxes. Based on these tax avoidance issues, this study tested using mining companies listed on the Indonesia Stock Exchange (BEI) as samples, because mining companies in Indonesia have high potential to practice tax evasion. The company data that was sampled in this study from 2012-2016. This study sought to find empirical evidence about the effect of corporate governance projected on the number of audit committees, the composition of independent board of commissioners and audit quality also by adding variables of profitability and liquidity.